使用对比法提高学生“一”和“不”变调的掌握能力以高中二年级为例 - Deasy Indrayani; Lily Thamrin; Bun Yan Khiong (Universitas Tanjungpura, 2019)
AbtractIn chinese language learning, the mastering in tone is really important. Beside the four tones, the changes of tone is also important. But there are still so many people who don’t understand even don’t know about this tone changes, especially the changes of “yi” and “bu”. To solve this problem, this study is aim to examine if the comparison method could help students in class XI MIA 1 and XI MIA 4 of Saint Peter Senior High School to learn about “yi” and “bu” tone changes in a easier and deeper way or not. Based on the data collected, with this comparison method, student not only understand but also mastering the tone changes of “yi” and “bu”. After the learning process, there is a significant progress about the test result. There are two parts in this test, the first part contains a simple phrase of “yi” and “bu” tone changes, has a progress at 26.64%, and the second part which contains sentences about “yi” and “bu” tone changes , has a progress at 16.53%. This means the method is really helpful in the learning “yi” and “bu” tone changes.Keywords : Excellence, Comparison Method, Tone Changes